Phase Transitions in Orthoenstatite and Subduction Zone Dynamics: Effects of Water and Transition Metal Ions. Issue 4 (13th April 2018) - Xu, Jingui; Zhang, Dongzhou; Fan, Dawei; Zhang, Jin S.; Hu, Yi; Guo, Xinzhuan; Dera, Przemyslaw; Zhou, Wenge
Abstract: Synchrotron‐based high‐pressure and temperature single‐crystal X‐ray diffraction experiments were conducted on two hydrous orthoenstatite samples (oEn#1: Mg1.004 Si0.996 O3, ~619 ppm water; oEn#2: Mg0.947 Ni0.055 Si0.998 O3, ~696 ppm water) to ~34 GPa and 700 K, using resistively heated diamond anvil cells. The α ‐opx ( Pbca space group)→ β ‐opx ( P 21 / c space group) phase transition of oEn#1 occurs at 12.90(2) GPa, and the β ‐opx phase persists to 34.25(1) GPa. The α ‐ β transition of oEn#2 occurs at 13.50(1) GPa, and a new isosymmetric β ‐opx→ β ‐opxII transition takes place at 29.80(4) GPa. The β ‐opxII phase is preserved down to 24.53(3) GPa during decompression. The transition to the monoclinic β ‐opxII phase is interpreted as a result of incorporation of Ni 2+ into the orthoenstatite structure. Fitting the third‐order Birch‐Murnaghan thermal equation of state to the single‐crystal P‐V‐T data yields the thermoelastic parameters of the α ‐ and β ‐opx phases for both orthoenstatite samples. This study is the first attempt to determine the thermal equation of state of the β ‐opx phase. Our results suggest that several hundred ppm of water has negligible effects on the bulk modulus of orthoenstatite but notably enhances the thermal expansion. The potential effects of metastable orthoenstatite on subduction zone dynamics are discussed, and the possible contributions of displacive phase transitions to enhancement of the transformational faulting mechanism of the deep‐focus earthquakes in subducted slabs are considered. The presence of metastable orthoenstatite within cold slabs could promote slab stagnation above the 660‐km discontinuity. Key Points: Single‐crystal X‐ray diffraction experiments are carried out on hydrous Mg end‐member and Ni‐bearing orthoenstatite(oEn) to 30 GPa and 700 K Several hundred ppm of water has negligible effects on the phase transition and bulk modulus of oEn but promotes the thermal expansion Ni 2+ strongly influences the phase transition of oEn and causes a different high‐pressure transition ( β ‐opx→ β ‐opxII) than that in Fe‐oEn